Analytical study of metal from the Petrovka Culture of Northern Kazakhstan - Kuzminykh Sergey V.; Degtyareva Anna D.; Artemyev Dmitry A.; Blinov Ivan A.; Orlovskaya Lyubov B. (Поволжская археология)
The results of spectral, mass spectrometric and energy-dispersive scanning electron microscopy analyzes of non-ferrous metal from the Petrovka culture of the XIX–XVIII centuries BC in Northern Kazakhstan are presented. The metal was mainly analyzed by spectral analysis in the 70s–80s of the XX century in the Laboratory of natural science methods of the Institute of Archaeology of the Russian Academy of Sciences. Since the collection is in the funds of the North Kazakhstan Museum of Regional Studies, sampling for modern types of analysis is excluded. The main purpose of the study is to identify geochemical and metallurgical groups with the possible identification of raw material sources and the main vectors of historical and metallurgical relations. Analysis of the main components of the chemical composition of element-impurities of copper and bronze artifacts proved the conclusion that more than 70% of the objects can be associated with local North Kazakhstan sources connected with copper-skarn/porphyry deposits of the Kokshetau anticlinorium. At the same time, the possible share of Ural metal in the collection could reach up to 30% of the studied inventory, which confirms the intensity of the trade exchange of metallurgical products between the Ural and Kazakhstan centers of metal production.